Constrained software and runtime system generation for embedded applications - Gupta, Rajesh K.; De Micheli, Giovanni 1955- (Univ. of Ill., Dep. of Computer Science, 1994)
Abstract: "In this paper we focus on the problem of synthesis of the software component of mixed system designs. Mixed systems are composed of interacting hardware components such as general-purpose processors and application-specific circuits and software components that execute on the general-purpose hardware. The software component consists of application- specific routines that must deliver the required system functionality and a runtime environment. Further, the software is required to deliver functionality under constraints on timing and memory stage available. We consider methods to achieve software generation under imposed constraints and demonstrate the utility of our approach by examples."
Keywords: Software engineering